DETERMINAN NILAI TUKAR RUPIAH TERHADAP DOLAR AMERIKA SERIKAT - Maidatun Maftukha (2022)
The exchange rate plays an important role in economic transaction activities used by international economis agents. Exchange rate movements have an impact on the economy, considering that internasional trade transactions use legal means of payment, namely the unit of currency value accepted by all countries. There are several factors that influence the movement of the rupiah exchange rate, especially macroeconomic factors. This study aims to analyze the effect on inflation, foreign exchange reserves, interest rate, and the trade balance on the rupiah exchange rate against the United States dollar. Secondary data in the form of time series data for the period 1985-202 is used in this study. The result of multiple regression testing state that inflation had no significant effect on the rupiah exchange rate, while foreign exchange reserves, interest rate, and the trade balance had a significant effect on the rupiah exchange rate.